Beta Adrenergic Blockade Is Feasible During Primary Treatment for Ovarian Cancer [10J]. Issue 1 (May 2017) - Ramondetta, Lois; Thaker, Premal; Hu, Wei; Urbauer, Diana; Chisholm, Gary; Sood, Anil
Abstract : INTRODUCTION: Adrenergic stimulation promotes EOC growth and metastasis. Nonselective beta-blocker (BB) women with EOC is associated with longer OS. The purpose of this study was to determine the feasibility of beta-adrenergic blockade in women with EOC during initial chemotherapy in a prospective clinical trial. METHODS: Women with suspected diagnosis of EOC, primary peritoneal or fallopian tube cancer with plan for tumor reductive surgery (TRS) or neoadjuvant chemotherapy were eligible. Patients (pts) began propranolol 10-20 mg BID 48 hrs prior to any treatment. QOL and serum levels of angiogenic cytokines were assessed. Random effect Tobit models were used to determine association between response and IL6, IL8 and VEGF. RESULTS: 32 pts enrolled, 6 ineligible leaving 26 for analysis. Of 26 pts, 8 did not complete 6 cycles on BB. Only 1 pt stopped due to fatigue after 4 days of BB. Eighteen pts (69%) completed all 6 cycles on BB; 69% were white. Mean age was 58; 80% were stage IIIC- IV, 30% were primarily debulked and 85% had optimal TRS. Serum IL 6, IL 8 and VEGF correlated with response (p < 0.0001). For 18 pts completing 6 cycles on BB, overall QOL, anxiety and depression improved significantly (p=.03). CONCLUSION: The impact of adrenergic stimulation on cancer growth is well documented and deserves further evaluation in a randomized setting. Use of propranolol during primary treatment of EOC, PP/FT cancer is feasible and potentially results in improved QOL.